PENGARUH PASAR SAHAM DUNIA TERHADAP PASAR SAHAM INDONESIA - Elvin Adityara (Faculty of Economic and Business, 2012)
This research was intended to analyze the causality of the global stock markets to Indonesian stock market. The variables of this research were used stock price indices from nine countries. This research using Granger Causality and VAR from 2004 up to 2010. USA, Japan, and England were selected because those countries had strong economics. The results, there are causality Granger among the global stock markets to Indonesian stock market.The global stock markets that has bi-directional causality were Australian stock market, England stock market, Singapore stock market, and Philipine stock market. Meanwhile, the global stock markets that has uni-directional causality were Japan stock market, USA stock market, Hongkong stock market, and Malaysia stock market.DOI: 10.15408/etk.v11i2.1887